Effects of exercise intensity and frequency on improving cognitive performance in middle-aged and older adults with mild cognitive impairment: A pilot randomized controlled trial on the minimum physical activity recommendation from WHO - Yu, Danny J.; Yu, Angus P.; Bernal, Joshua D. K.; Fong, Daniel Y.; Chan, Derwin K. C.; Cheng, Calvin P.; Siu, Parco M. (Frontiers in Physiology, 2022)
Background: The World Health Organization physical activity guidelines recommend adults and older adults to accumulate at least 150-300 minutes of moderate or 75-150 minutes of vigorous aerobic-type physical activity weekly for health benefits including improvements of cognitive performance. However, the optimal exercise intensity and frequency for maximizing the cognitive benefits remain unclear. Purpose: We conducted a parallel, assessor-blinded, pilot randomized controlled trial to evaluate the effectiveness of different intensities and frequencies of the WHO-recommended minimal volume of aerobic-type physical activity on improving cognitive performance in middle-aged and older adults with mild cognitive impairment (MCI). Methods: Participants were randomly allocated to the stretching exercise control group (CON), once-a-week and thrice-a-week moderate-intensity walking groups (M1 and M3), and once-a-week and thrice-a-week vigorous-intensity walking groups (V1 and V3). Intervention duration was 12 weeks. The primary outcome was global cognitive performance assessed by the Hong Kong version of Montreal Cognitive Assessment. Secondary outcomes were self-report and objective cognitive performances, mental health, sleep quality, and cardiorespiratory fitness. Results: Thirty-seven participants completed the study (CON: n=7, M1: n=7, M3: n=7, V1: n=8, V3: n=8). Participants in all four walking exercise groups demonstrated significant improvements in global cognitive performance assessed by the Hong Kong version of the Montreal Cognitive Assessment after the intervention when compared to CON (p<0.001). The walking exercise interventions also significantly mitigated the anxiety severity (p<0.005) and improved the cardiorespiratory fitness (p<0.05) of the participants in the walking exercise groups. Conclusion: 150-minute moderate- or 75-minute vigorous- intensity walking exercise performed once- or thrice- weekly showed similar effects on improving cognitive performance in middle-aged and older adults with MCI. The 12-week walking exercise interventions also reduced anxiety severity and improved cardiorespiratory fitness of the participants.